NEW DIRECTIONS OF LABOR MIGRATION FROM TAJIKISTAN TO THE PERSIAN GULF COUNTRIES: DEVELOPMENT TRENDS AND PROSPECTS - A. Kh. Rakhmonov (Вестник университета)
Currently, labor migration from Central Asian countries is acquiring new geographical and socio-demographic dimensions, and migration flows are being reoriented to new directions and regions. The article considers the factors and scale of emigration from Tajikistan, the reasons for the reorientation of Tajik migrants from Russia to the Persian Gulf countries, as well as interstate agreements between Tajikistan and the Persian Gulf countries in the field of labor migration regulation. The author cites economic and geopolitical factors as the reasons for the changes: on the one hand, the fall in the ruble exchange rate and the decline in the level of wages in ruble terms, the tightening of migration policies in Russia and Kazakhstan force some migrant workers to look for new directions for migration; on the other hand, the participation of public and private labor agents is becoming more active.